Impact of temporary frozen storage on the safety and quality of four typical Belgian bakery products. (February 2021) - Van Bockstaele, Filip; Debonne, Els; De Leyn, Ingrid; Wagemans, Kathou; Eeckhout, Mia
Abstract: EU regulation No. 1169/2011 states that foods that have been frozen and thawed before being sold, the name shall be accompanied by the designation 'defrosted'. This requirement does not apply when defrosting has no negative impact on their safety and quality. Producers should be able to show that defrosting has no negative impact during the shelf-life. Therefore, the impact of temporary frozen storage on the quality and safety of industrially produced bakery products, including wholemeal bread, sandwich rolls, sponge cake and pie, was studied in comparison with non-frozen products. Total plate count, aw, texture analysis and sensory analysis were applied to assess microbial, physico-chemical quality and consumer acceptability of the products. All tests were performed before and after the defrosted shelf-life period. Freezing and defrosting of bakery products did not enhance microbial spoilage. All values remained under the maximal limit of microbial contamination, respectively 5 log CFU/g for bread products and 4 log CFU/g for sponge cake and pie. Texture analysis and aw showed only limited differences between fresh and defrosted products. Although a slight difference in texture was observed for sandwich rolls, sponge cake and pie through sensory trials, all products were found acceptable for consumption. Highlights: The impact of temporary frozen storage and thawing of various bakery products was evaluated. Quality of wholemeal bread, sandwich rolls, sponge cake and pie was assessed during shelf-life. Temporary frozen storage and thawing did not enhance microbial spoilage of bakery products. Crumb hardness of bread and sandwich rolls was not impacted by temporary freezing. Sensory trials showed no reduced acceptability rates of temporary frozen compared to non-frozen bakery products.